Peran Motivasi Guru Dalam Meningkatkan Hasil Belajar Siswa Materi Pendidikan Agama Islam Di SD Muhammad Al-Unaizy - Irwan Desiharto; Dede Maulana Malik; Siti Qomariyah (Universitas Palan, 2024)
One of the problems in learning is that teachers rarely motivate students, and students are not motivated. Finally, students are less motivated and their learning outcomes are not achieved well. The research aims to determine student learning motivation in improving learning outcomes, student learning outcomes in PAI lessons before and after getting motivation, and determine the role of PAI teacher motivation in improving student learning outcomes. This research uses field research with descriptive qualitative methods. Data collection techniques were carried out using observation, interviews and documentation in the field. This research was conducted at Muhammad Al-Unaizy Elementary School. The results of this research show that providing motivation before studying at SD Muhamad Al-Unaizy has gone well. Thus, this motivational activity can improve student learning outcomes at the end of the meeting. Supporting factors in this activity include parental support, adequate infrastructure. The inhibiting factor is the level of students' varying levels of absorption in absorbing motivation from the teacher.